Tecnologias assistivas no ensino de termoquímica numa perspectiva inclusiva - Rodrigues, Bruno César Barbosa (2023)
The existing challenges in the classroom for the teaching of Chemistry, mainly with regard to the subject of thermochemistry, combined with the great difficulty that students have in performing the abstraction of the chemical contents taught, still present a new obstacle: the development of resources pedagogical methods with the objective of including students with visual impairments in the school context, whose success depends on concrete and well-founded tools for the construction of scientific knowledge. For these reasons, the present work aims to analyze the use of assistive technologies in the teaching of thermochemistry in the construction of chemical knowledge for visually impaired students from an inclusive perspective. This study was developed with the collaboration of 4 (four) second-year high school Chemistry teachers who teach classes for students with visual impairment (blindness and/or low vision). This research is characterized as a case study and was carried out in the descriptive and field modality. The methodology used was of a qualitative nature, and the data obtained were through the content analysis proposed by Bardin (2016). The present work is organized and structured in the multipaper format, composed of three scientific articles. The first article consists of a systematic mapping of academic works on assistive technologies related to the teaching of Thermochemistry. The second article is a semi-structured interview with chemistry teachers from the second grade of high school in the state education network of Alagoas, with the purpose of identifying the difficulties in adapting classes in teaching thermochemistry from an inclusive perspective. The third article consists of the application and evaluation of inclusive graphics for teaching thermochemistry in a second grade high school class. The results showed that, in the last ten years, research on assistive technologies and the teaching of thermochemistry involving students with visual impairment is a little explored area, however, only two scientific articles were found related to the referred theme and no research work. dissertation or thesis on the subject. Also, there were numerous challenges and difficulties regarding the teaching of thermochemistry to this public of students, such as the lack of practical training, which is often non-existent during graduation, and the construction and/or adaptation of accessible pedagogical resources. and tactile for teaching this content. In addition, it was verified that the use of inclusive graphics associated with strong colors and language in Braille and Portuguese facilitated the reading and understanding of chemical representations by students, allowing the creation of mental representations that increased communication and access to scientific language through of the senses and the materials used. These results allowed us to suggest the need to carry out research that encourages new discussions about the training of Chemistry teachers, as well as the construction of inclusive educational practices.